2017
DOI: 10.1155/2017/4024672
|View full text |Cite|
|
Sign up to set email alerts
|

The Parenteral Vitamin C Improves Sepsis and Sepsis-Induced Multiple Organ Dysfunction Syndrome via Preventing Cellular Immunosuppression

Abstract: Cellular immunosuppression appears to be involved in sepsis and sepsis-induced multiple organ dysfunction syndrome (MODS). Recent evidence showed that parenteral vitamin C (Vit C) had the ability to attenuate sepsis and sepsis-induced MODS. Herein, we investigated the impact of parenteral Vit C on cellular immunosuppression and the therapeutic value in sepsis. Using cecal ligation and puncture (CLP), sepsis was induced in WT and Gulo−/− mice followed with 200 mg/Kg parenteral Vit C administration. The immunolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 29 publications
(53 reference statements)
0
38
0
3
Order By: Relevance
“…Subsequently, Fisher et al (21) also showed that intraperitoneal injection of AsA in AsA-deficient knockout mice (Gulo2/2 mice), which are unable to synthesize AsA, suppressed injuries to the lung, kidney, and liver produced during sepsis caused by fecal stem solution. Recently, another group (22) reported that parenteral AsA attenuated the symptoms of sepsis and inhibited the immunosuppression of regulatory T cells in Gulo2/2 mice with cecal ligation and puncture. As a noteworthy result, a human phase I trial showed that intravenous AsA infusion reduced the severe organ failures in septic patients (16).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Fisher et al (21) also showed that intraperitoneal injection of AsA in AsA-deficient knockout mice (Gulo2/2 mice), which are unable to synthesize AsA, suppressed injuries to the lung, kidney, and liver produced during sepsis caused by fecal stem solution. Recently, another group (22) reported that parenteral AsA attenuated the symptoms of sepsis and inhibited the immunosuppression of regulatory T cells in Gulo2/2 mice with cecal ligation and puncture. As a noteworthy result, a human phase I trial showed that intravenous AsA infusion reduced the severe organ failures in septic patients (16).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research in wild-type and Gulo knockout mice indicated that parenteral administration of 200 mg/kg vitamin C modulated the immunosuppression of regulatory T-cells (Tregs) observed in sepsis [ 89 ]. Vitamin C administration enhanced Treg proliferation and inhibited the negative immunoregulation of Tregs by inhibiting the expression of specific transcription factors, antigens, and cytokines [ 89 ]. The mechanisms involved likely rely on the gene regulatory effects of vitamin C [ 79 , 89 , 199 , 200 ].…”
Section: Vitamin C and Leukocyte Functionmentioning
confidence: 99%
“…Moreover, vitamin C supplement of 200 mg/day for 1–3 months increased IgG and IgM serum levels and improved humoral immune response in elderly [ 43 ]. An animal study showed that vitamin C inhibited the negative immunoregulatory effect of T regulatory cells, which in turn enhanced T cell-medicated response leading to improvement of sepsis and sepsis-induced multi-organ failure [ 11 ]. Vitamin C modulates the release of various inflammatory mediators.…”
Section: Immunomodulatory Effect Of Vitamin Cmentioning
confidence: 99%
“…Sepsis leads to cellular immunosuppression. Treatment of mice with high dose (200 mg/kg) of IV vitamin C inhibited the negative immunoregulatory effect of T regulatory cells, which in turn enhanced T cell-mediated cellular immune response, and resulted in improvement of sepsis and sepsis-induced multi-organ dysfunction syndrome [ 11 ]. Therefore, vitamin C could be beneficial as a supportive treatment of sepsis and septic shock, which are common complications associated with COVID-19.…”
Section: The Role Of Vitamin C In Management Of Ards Sepsis Septic mentioning
confidence: 99%